The frequency-amplitude gradient in the sleep EEG of children and its diagnostic significance - Aucélio, Carlos Nogueira (2007)
OBJECTIVE: 1014 EEGs of children in the 3-months to 12-years age group were obtained during sleep with the purpose of assessing the frequency and amplitude gradient (FAG) its absence thought to be an indicator of neurological disorder. METHOD: FAG findings were divided into present/absent. The neurological findings were classified according to the presence (abnormal neurological finding-ANF) or absence (normal neurological finding-NNF) of neurological disorder. The association and significance between FAG and neurological findings was determined by prevalence ration (PR) and chi-square test (chi2). RESULTS: FAG showed a characteristic distributions of voltage output during non-REM sleep, stage II, in the 3-months to 5-years age group with NNF. The PR and the chi2 test demonstrated a strong association between FAG absent and ANF. CONCLUSION: FAG is an age-dependent EEG sleep parameter and absence of FAG in the 3-months to 5-years age group is highly suggestive of neurological disorder.